Experiência e educação : contribuições de Paulo Freire para a educação de pessoas jovens e adultas. - Franzi, Juliana (2007)
This work integrates the research line Social Practices and Educational Processes that includes the education as a wide process, not restricted to the school world. Claiming such comprehension was of fundamental importance to this research, once it searched understand the richness of the human beings existential experiences, inserting the most different social practices. Paulo Freire, one of the main references of the research line and the main of this work, attributed to experience a great educational potential, being the place of construction of the knowledge of the done experience . Approaching the theme meant dealing with questions that require an attentive look, given the disqualification done in the modern societies of the experiences of certain individuals, groups and nations. That s why it s necessary to recognize the need of showing the worth of the knowledge along that was unfairly marginalized. This study is not about despising school education role due to the fact education is understandable as a wide process, but to reflect about its function and the possibility of relation with the existential experience of the learners. The research is dedicated to the investigation of the relation between experiences concepts and education in Paulo Freire s works, having as objectives identify in the author s documents such concepts and the relation between them, as well as verify the world reading learners of Youngsters and Adults Education have about such constructed concepts in a experienced way. So it was carried out a review of the authors works that helped in the comprehension of their thought. Besides, I inserted myself and participated, while researcher, in Youngsters and Adults Education (EJA), term II, equivalent to 3º and 4º grade of fundamental teaching in order to enlarge the comprehension of concepts adding also the book reading to the existential source during three months, I inserted myself in a Youngsters and Adults Education classroom, participating in twenty two meetings writing a field, as well as, carrying out interviews with five learners and a forum video of techniques collection that belong to Communicative Investigation Methodology. From these procedures on, the participants world readings could be revealed to me about experience, education and school education leading me to understand better such concepts in the Paulo Freire s works, as well as, the relation between them. The knowledge of the done experience showed me in the study as a synthesis of the meeting between experience and education, demanding, however, dialogue for the construction of a comprehension criticism about the reality. Therefore, we understand the main contribution of the present work for Education, Teaching Methodology and Youngsters and Adults Education is the statement of the respect to mistakenly link between experience and the women and men, adults and youngsters education get involved without forgetting the intention and the dialogue that are fundamental to become criticism and independent.